2002
DOI: 10.1038/sj.mn.7800126
|View full text |Cite
|
Sign up to set email alerts
|

T-Lymphocytes Modulate the Microvascular and Inflammatory Responses to Intestinal Ischemia-Reperfusion

Abstract: These findings indicate that intestinal I/R is associated with the recruitment of CD4+ and CD8+ T-cells, which is mediated by endothelial MAdCAM-1. T-cells seem to modulate the recruitment of neutrophils that occurs hours after reperfusion as well as the increased albumin extravasation that occurs within minutes after reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 0 publications
1
35
1
2
Order By: Relevance
“…However, our data demonstrates that, in the first hours following intestinal IR, αβ T cells do not significantly contribute to the acute injury. Our findings are seemingly in opposition to existing studies that have suggested an involvement of T cells in intestinal IRI: Studies in SCID mice demonstrated protection from intestinal IRI [14,27,33]. Shigematsu and colleagues reported a significant reduction in the intestinal leakage of albumin compared to the WT and restoration of the WT levels of albumin extravasation was reported in SCID mice reconstituted with T cells from WT mice.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, our data demonstrates that, in the first hours following intestinal IR, αβ T cells do not significantly contribute to the acute injury. Our findings are seemingly in opposition to existing studies that have suggested an involvement of T cells in intestinal IRI: Studies in SCID mice demonstrated protection from intestinal IRI [14,27,33]. Shigematsu and colleagues reported a significant reduction in the intestinal leakage of albumin compared to the WT and restoration of the WT levels of albumin extravasation was reported in SCID mice reconstituted with T cells from WT mice.…”
Section: Discussioncontrasting
confidence: 99%
“…The effects observed in that study were rather mild with a relative change of 10% and the applied reperfusion time with 6 hours longer than in our model, thus may explaining the minor differences between their findings and that of the current study [13]. Nevertheless, the question of the T cell influx in intestinal IRI remain unresolved as influx kinetics in the literature are discrepant: One further study showed an increase of CD4 + (αβ) T cells in the gut 1h after ischemia (but not after 3 hours of reperfusion) compared to control mice, while another found no difference 1 hour after reperfusion but a peak of T cells after 6 hours of reperfusion [14,27]. We assume that the different mouse strains and different methodological approaches utilized in these studies may account for the inconsistencies.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations